A Maranao dictionary - Macaraya, Batua A.; McKaughan, Howard P. 1922- (De La Salle University Press, [and] Summer Institute of Linguistics, 1996)
It includes 8,500 Maranao entries to be able to give the prototypical meaning of Maranao which are either base words or derivations. It also contains an introduction on the grammar of Maranao, to aid the user in identifying base forms. It is more a glossary than a dictionary.